Penggunaan Metode Demonstrasi Berbantuan Mega OTT Pemerintah Untuk Meningkatkan Aktivitas dan Prestasi Beajar - Setyawati, Dwi (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2019)
This research aims to improve the activities and achievements of the study material autonomous region through the use of methods of assisted demonstration Mega OTT Government. Research subject learners class 9B SMP Negeri 4 Salatiga Years Lessons 2017/2018. The research is the research of class action is carried out in 2 cycles. Data collection with the non-engineering tests and tests. An examination of the validity of the data by triangulation, checking with colleagues, friends and the use of an accurate reference. Data analysis with descriptive statistical analysis. Observation results against learning activities on cycle I achieve score 3.7 percentage of 73.6% and activity cycle II score 4.1 percentage 80% activity. The average value of the learning achievements of pre-cycle 66.7 number of learners who complete the KKM 30% from 30 children. The average results of achievement learning cycle I 80.0 and comprehensively reach 66.7%, KKM cycle II averaging 83.7 83.3% and finished the KKM. Thus declared the application of the method of demonstration Mega-assisted the Government can increase the activity of OTT and the learning achievements of students.